Authority of the Tangerang City Manpower Office in Social Empowerment for Job Training for Persons with Disabilities in Tangerang City Based on Tangerang City Regional Regulation Number 3 of 2021 Concerning Respect, Protection and Fulfillment of the R - O. R., Ananda Dita Kurnia; Jazuli, H.E. Rakhmat (Universitas Sultan Ageng Tirtayasa, 2023)
The social stigma that persons with disabilities cannot work as effectively as ordinary employees makes the government have to guarantee the rights of persons with disabilities which aim to provide equal opportunities, respect, fulfillment and protection of the rights of persons with disabilities in social life, including in job training. The purpose of this study is what are the authorities and constraints of the Tangerang City Employment Service in implementing the Social Empowerment Policy for Job Training for Persons with Disabilities in Tangerang City based on Tangerang City Regional Regulation Number 3 of 2021 concerning Respect, Protection and Fulfillment of the Rights of Persons with Disabilities? The method used in this research is empirical juridical with data analysis through a qualitative approach using primary data in the form of interviews with Manpower Office officials and secondary data. The results of this research are that the social empowerment authority for persons with disabilities is carried out by the Manpower Office in the form of job training at the UPT BLK of the Employment Service which has not been implemented optimally where the Disability Service Unit has not yet been implemented. In conclusion, the authority of the Department of Manpower in empowering persons with disabilities, which is a source of authority for delegations, has not been fully implemented. The obstacles faced are the inactivity of the Disability Service Unit, the socialization of job training for persons with disabilities is still lacking, the factor is the lack of job training education for the community, especially persons with disabilities, and facilities and infrastructure that meet disability standards are still lacking.